The Concept of Open Legal Policy in Constitutional Court Decision No. 90/PUU-XXI/2023 on the Age Limit for Candidates for President and Vice President - Sabar Indra Husni; Hedwig Adianto Mau; Rotua Valentina Sagala (Transpublika Publisher, 2025)
Article 6A paragraph (5) of the 1945 Constitution of Indonesia affirms the principle of open legal policy by stipulating that the procedures for the election of the President and Vice President must be regulated by law. This provides space for the legislature to regulate various provisions related to elections, while the Constitutional Court acts as an interpreter of the constitution. This study aims to analyze the application and suitability of the concept of open legal policy in the Constitutional Court Decision Number 90/PUU-XXI/2023 concerning the age limit of candidates for President and Vice President. The study employs normative legal research techniques with a qualitative juridical analysis perspective, utilizing secondary data, tertiary legal resources, and primary data for reinforcement. The theory of authority and trias politica (division of powers) is used to analyze the examined decision. The results showed that the Constitutional Court in Decision No. 90/PUU-XXI/2023 was inconsistent in deciding cases, even though the articles tested were the same and the legal considerations and rulings were similar. Therefore, it is recommended that the Constitutional Court be more consistent in issuing decisions, especially those related to open legal policies. Strengthening the capacity of Constitutional Court judges is also needed to better understand the authority and division of powers within the framework of the 1945 Constitution of the Republic of Indonesia. In conclusion, the application of the concept of open legal policy needs to be implemented consistently and wisely to maintain legal stability in Indonesia.